A System for Data-Driven Programming of Multicomputers - Gaudiot, Jean-Luc; Ventre, Giorgio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1992)
Distributed systems are a promising solution to increase the computational power and fault-tolerance capabilities currently available in traditional computer architectures. While it is technologically possible to integrate large numbers of processors to form a single parallel machine, new approaches to the programming of such machines are needed. Indeed one of the major problems is to offer a programming model independent from the physical architecture and topology of parallel systems. The data-driven approach seems to be a good candidate for such a model, but requires an implementation able to bide the architectural complexity of a multicomputer. In this paper we show how we applied these principies to a Transputer-based parallel system and the characteristics of the resulting programming environment.